Isolation and primary identification of endophytic fungi from Cephalotaxus mannii trees - Pramuan Saithong (Maejo International Journal of Science and Technology, 2010)
Fifty-two isolates of endophytic fungi were collected from the bark of Cephalotaxus mannii (plum-yew) trees located in the north of Thailand and the south of China. All isolates were identified based on colony morphology and examination of spores and fruiting bodies using stereo and light microscopes. Thirty-five isolates (67.3%) belonging to 13 genera were recorded, viz. Cladosporium sp., Acremonium sp., Trichoderma sp., Monilia sp., Fusarium sp., Spicaria sp., Humicola sp., Rhizoctonia sp., Cephalosporium sp., Botrytis sp., Penicillium sp., Chalaropsis sp. and Geotrichum sp., while 17 strains (32.7%) were unidentified. The dominant genera found both in northern Thailand and southern China were Acremonium sp., Monilia sp. and Fusarium sp. Cladosporium sp. and Trichoderma sp. were found only in southern China, whereas Spicaria sp., Humicula sp., Rhizoctonia sp., Botrytis sp., Penicillium sp., Geotrichum sp., Chalaropsis sp. and Cephalosporium sp. were found only in northern Thailand. Thus, there seemed to be a significant difference in the genera of endophytic fungi from Cephalotaxus mannii trees of different sources.